The investigation of hippocampus and amygdala volume changes with MRI in patients with social anxiety disorder - Koc, Mustafa; Kuloglu, Omer Cihat; Yildirim, Hanefi; Atmaca, Murat (Cumhuriyet Univ Tip Fak Psikiyatri Anabilim Dali, 2018)
Objective: The purpose was to investigate the volume changes of hippocampus and amygdala in Social anxiety disorder (SAD) patients and healthy subjects. Methods: A total of 22 patients diagnosed with SAD, who were being treated as either inpatients or outpatients at the psychiatric clinic of our hospital, were enrolled in the study. The control group consisted of a total of 20 healthy volunteers who don't have exclusion criteria. Exclusion criteria were as follows: the presence of depression and other comorbidities, severe systemic diseases including diabetes mellitus, chronic renal failure, and hypertension, a low level of education preventing a healthy interview, and the presence of mental retardation. No preliminary preventive measures were implemented before imaging. The volume of hippocampus and amygdala in all patients was measured on MRI examinations. No intravenous contrast agent was administered. Results: The mean volume of right hippocampus and left hippocampus in patient group were 3.47 +/- 0.57 cm(3) and 3.44 +/- 0.48 cm(3), respectively. The mean volume of right hippocampus and left hippocampus in control group were 3.00 +/- 0.24 cm(3) and 2.98 +/- 0.27 cm(3), respectively. The right and left hippocampus volume of patient group was significantly higher than control group. The mean volume of right and left amygdala in patient group were 2.05 +/- 0.36 cm(3) and 2.04 +/- 0.37 cm(3), respectively. The mean volume of right and left amygdala in control group were 2.03 +/- 0.25cm(3) and 1.98 +/- 0.33 cm(3), respectively. The amygdala volume of patient and control group was not significantly different. By the way the correlation of amygdala in patient group was impaired. Conclusion: Our study revealed abnormalities of amygdala and hippocampus which may be associated with physiopathology of SAD.
Sosyal anksiyete bozukluğu hastalarında MRI ile hipokampus ve amigdala volüm değişikliklerinin araştırılması
Keywords: social anxiety disorder; hippocampus; amygdala; MRI volume